2005
DOI: 10.1109/tit.2005.858977
|View full text |Cite
|
Sign up to set email alerts
|

Distance Distribution of Binary Codes and the Error Probability of Decoding

Abstract: Abstract-We address the problem of bounding below the probability of error under maximum-likelihood decoding of a binary code with a known distance distribution used on a binarysymmetric channel (BSC). An improved upper bound is given for the maximum attainable exponent of this probability (the reliability function of the channel). In particular, we prove that the "random coding exponent" is the true value of the channel reliability for codes rate in some interval immediately below the critical rate of the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…To some extent, such combining was performed in [12,13]; however, the approach of [11] was used there not in the best way. Moreover, the most important proofs (concerning some variation problems) in [12,13] were based on purely numerical computations (without an analytical support), which makes it difficult to verify them.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, such combining was performed in [12,13]; however, the approach of [11] was used there not in the best way. Moreover, the most important proofs (concerning some variation problems) in [12,13] were based on purely numerical computations (without an analytical support), which makes it difficult to verify them.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Moreover, the most important proofs (concerning some variation problems) in [12,13] were based on purely numerical computations (without an analytical support), which makes it difficult to verify them.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Moreover, closed-form parametric expressions of the improved lower bound and its corresponding condition are provided in [57] for systems with equidistant DMCs. 5 In light of the recent work in [11], where the random coding exponent E (R; W ) of the BSC is shown to be indeed the true value of the channel error exponent E(R; W ) for code rates R in some interval directly below the channel critical rate (in other words, it is shown that for the BSC with its " above a certain threshold, E (R; W ) = E(R; W ) for R R C where R can be less than R (W ) [11]), we note via (1) and the lower bound in (22) and (23) that region B B B where E is exactly known can be enlarged. B and C C C. In A A A, E = 0.…”
Section: Observation 4 (Csiszár's Expurgated Lower Bound)mentioning
confidence: 97%
“…Namely, we apply result of Kalai and Linial [11,Proposition 3.2]: For every β with h(β) ≤ R there exists a sequence ǫ n → 0 such that for every code C of rate R there is a ξ 0 satisfying (14) such that…”
Section: A Proof Of Theoremmentioning
confidence: 99%